ANALISIS PENENTUAN HARGA POKOK PRODUKSI MENGGUNAKAN METODE FULL COSTING PADA UMKM PERCETAKAN CV. GRAFIKA - Anis Suriani; Anita Nursanti; Yuliana Adityaningsih; Suryasmira Suryasmira (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2026)
This study aims to analyze the calculation of the cost of goods manufactured (COGM) using the full costing method at CV. Grafika. The data used in this study consist of qualitative and quantitative data obtained through interviews, observations, and documentation of production costs in October 2024. The analytical method applied is descriptive analysis. The results show that the cost of goods manufactured calculated by the company has not included all production cost components, particularly fixed manufacturing overhead costs. Based on the full costing method, the cost of goods manufactured per unit of paper bag is Rp11,975, which is higher than the company’s calculation, with a difference of Rp1,553 per unit. This difference occurs because the full costing method includes all production costs, both variable and fixed. With a selling price of Rp20,000 per unit, the company still earns a gross profit. Therefore, the full costing method is considered more appropriate for calculating the cost of goods manufactured at CV. Grafika